Synthesis of Heterocycles by HNTf2-Catalyzed C–H Functionalization of Vinyldiazo Compounds with 3-Phenyl-3-hydroxyisoindolinone - Bao, Ming; Arman, Hadi; Doyle, Michael P. (Synthesis, 2024)
A Brønsted acid catalyzed C–H functionalization of vinyldiazoacetates with 3-hydroxyisoindolinone is developed. This methodology provides a general access to E-substituted isoindolinone vinyldiazo compounds in good yields and excellent diastereoselectivities with broad substrate generality under mild conditions, and with 4-substituted 2-diazo-3-butenoates produces fused bicyclic pyrrolidines. The reaction generally involves addition of the N-acyl ketiminium electrophile, formed from the 3-hydroxyisoindolinone, to the vinylogous position of the vinyldiazo compound resulting in vinyldiazonium ion intermediates that undergo deprotonation to new vinyldiazo compounds or ring closure to fused bicyclic pyrrolidines.
Keywords: Brønsted acid catalysis; vinyldiazo compound; electrophilic addition; C–H functionalization; heterocycles